The bleeding mother and her baby: a study to determine the fetomaternal outcome in cases of placenta previa - Lewis, Preeti Frank; Bijapur, Sana Tarannum; Gurnani, Deepika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Placenta previa is one of the major causes for obstetric hemorrhagic morbidity and mortality with increasing incidence in recent times. This study aims at determining risk factors, maternal and fetal outcome associated with placenta previa. Methods: This was an observational, retrospective study conducted at a tertiary care hospital in Mumbai from May 2017 to March 2020. A total of 102 women with placenta previa during the study period were included, their case records critically analyzed to identify risk factors, maternal outcome in relation with blood transfusion required, ICU admission, obstetric hysterectomy and fetal outcome pertaining to prematurity, asphyxia and mortality. Results: A total of 102 patients were analyzed. Placenta previa was more common in >26 years of age, multipara (64.7%), with previous history of caesarean sections (21.5%) and previous curettage (11.7%), 44.2% babies born were preterm, 4.4% stillbirths and 8.5% neonatal deaths. Maternal complications like antepartum hemorrhage was seen in 58.8% patients and postpartum hemorrhage in 33.3%, blood transfusion was required in only 18 patients post operatively, bladder rent was seen in 3 patients and there was no maternal mortality. 44 patients required uterine artery ligation, Ashok Anand stitch was taken in 37 patients, uterus compression sutures in 10, obstetric hysterectomy in 7 patients and internal iliac artery ligation in 2 patients. Conclusions: Early identification of women at risk, obstetric preparedness and simple techniques like uterine artery ligation, Ashok Anand stitch and uterine compression sutures can help in effectively reducing need for multiple blood transfusions and morbidity.